High similarity in bacterial bioaerosol compositions between the free troposphere and atmospheric depositions collected at high-elevation mountains. (15th April 2019) - Triadó-Margarit, Xavier; Caliz, Joan; Reche, Isabel; Casamayor, Emilio O.
Abstract: The long-range transport of bioaerosols takes place in the free troposphere and has lately gained a renewed interest in both environmental and health-related disciplines. Sampling free troposphere bioaerosols has been, however, historically challenging and requires of expensive and complex facilities. We analysed different bacterial bioaerosols studies carried out by sequencing of the 16S rRNA gene, available from the literature. The dataset was compared with bacterial bioaerosols present in rain and dry deposition passively collected at high-elevation sites in Sierra Nevada along a set of sampling periods lasting 3 years. Up to 65% of OTUs and 82% of the bacterial genera were shared between wet and dry bioaerosols. Interestingly, only Oxalobacteraceae were notably more abundant in wet deposition, with Noviherbaspirillum and Massilia as dominant genera. We demonstrated that the bacterial composition of bioaerosols collected by passive natural deposition at high-elevated mountains were closer to the bacterial microbiome from the free troposphere. Interestingly, the meta-analysis showed a different bacterial composition and community structure in bacterial bioaerosols collected at low-elevated areas, over the open ocean, or during desert dust events. Since the boundary layer can be easily reached in high mountain areas, and the local landscape is surrounded by rocks and meadows, alpine stations are potentially optimal research sites with reduced influence of surface aerosols, minimizing local contaminations. Consequently, sampling alpine bioaerosols could be a good proxy for bioaerosols monitoring, long-range dispersal studies, and the dynamic characterization of the free troposphere microbiome. Highlights: Different bacterial bioaerosols exist at high-elevation mountains, low lands, over the open ocean, or during desert dust events. Bacterial bioaerosols ground-sampled above the boundary layer were largely convergent with the free troposphere microbiome. Airborne sampling stations at high-elevation mountains are a good proxy for long-term monitoring of the globally transported microbiome.